The Development of Adaptive Collaboration in a Dynamic Environment for Information Sharing - Adigun, A. A.; Osofisan, A. O.; Robert, A. B. C.; Kolawole, M. O. (Current Topics on Mathematics and Computer Science Vol. 4, 2021)
To track problem-solving methods, collaborative systems are utilised in the learning environment. Collaboration is both a process and an outcome in which shared interest, or key stakeholders address conflict that cannot be addressed by any single individual. Collaborative systems that had previously been created were primarily focused with the evolutions and contributions in a dynamic environment. When evolution and dynamism are encouraged, however, information sharing among participants is often compromised, a concern that has not been adequately addressed. In this work, Adaptive collaborative systems have been developed that allowed for the reuse of information in a dynamic setting while reducing participant compromise. The amount of time available for adaptive collaboration in a dynamic environment for the sharing of information was increased.